2001
DOI: 10.2172/965675
|View full text |Cite
|
Sign up to set email alerts
|

Polymers for Chemical Sensors Using Hydrosilylation Chemistry

Abstract: SummarySorbent and functionalized polymers play a key role in a diverse set of fields, including chemical sensors, separation membranes, solid-phase extraction techniques, and chromatography. Sorbent polymers are critical to a number of sensor array or "electronic nose" systems. The responses of the sensors in the array give rise to patterns that can be used to distinguish one compound from another, provided that a sufficiently diverse set of sensing materials is present in the array. Figure S1 illustrates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…BPA-HMTS and BPA-PDMS are polymers which are synthesized at Marquette University using a hydrosilylation reaction of BPA and HMTS, and BPA and PDMS, respectively [39,40]. BPA is the organic chemical that provides the functional group for the analyte/coating interaction to take place.…”
Section: Polymersmentioning
confidence: 99%
“…BPA-HMTS and BPA-PDMS are polymers which are synthesized at Marquette University using a hydrosilylation reaction of BPA and HMTS, and BPA and PDMS, respectively [39,40]. BPA is the organic chemical that provides the functional group for the analyte/coating interaction to take place.…”
Section: Polymersmentioning
confidence: 99%
“…16 Vapor sorption (gas-phase sensing) as a function of these interactions has been systematically examined using linear solvation energy relationships (LSERs). 12,17,18 Although LSERs has been performed for gas-phase sensing, the results can be used in aqueous environments as starting points to design polymer structures to promote particular interactions for improved sensitivity and selectivity. It is noted that, in liquid-phase sensing, the partition coefficient of the analyte-coating pair, a function of the LSERs, also depends on the analyte solubility.…”
mentioning
confidence: 99%
“…A consideration of the chemical structures that lead to hydrogen-bond acidity leads to a choice of fluorinated alcohols and phenols as the functionality that should be incorporated into a polymer. 18,19 Furthermore, studies done by Abraham et al 20 to compare hydrogen-bond acidities of several propyl-or allyl-substituted bisphenol structures using inverse gas chromatography and LSERs showed that fluorinated bisphenol-A structures were more hydrogenbond acidic than non-fluorinated analogues. 18,20 These considerations provide the design criteria for the synthesis of the hybrid organic/inorganic sensing layer, bisphenol A-hexamethyltrisiloxane (dubbed BPA-HMTS), used in this work.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 The methyl-substituted carbosiloxane polymer is a non-polar material that can adsorb aliphatic hydrocarbons. 17,18 The phenyl-substituted cabosiloxane is a polarized polymer sensitive to aromatic hydrocarbons. 19 Polystyrene and its derivatives are the most widely used polymeric materials as sorbents in sensors and various analytical techniques.…”
mentioning
confidence: 99%